Comment on: Intrapulmonary shunt and alveolar dead space in a cohort of patients with acute COVID-19 pneumonitis and early recovery. Issue 2 (9th February 2023) - Ackermann, Maximilian; Tafforeau, Paul; Brunet, Joseph; Kamp, Jan C.; Werlein, Christopher; Kühnel, Mark P.; Jacob, Joseph; Walsh, Claire L.; Lee, Peter D.; Welte, Tobias; Jonigk, Danny D.
With the greatest interest we read the paper by Harbut et al. [1] describing the role of intrapulmonary shunting and alveolar dead space in patients with acute COVID-19 pneumonitis. We are grateful for them sharing their valuable functional blood and alveolar gas exchange data, pointing out a significant alveolar dead space of nearly 30% in recovered COVID-19 patients, suggesting a persistent pulmonary vascular pathology. Although COVID-19 related hypoxaemia is characterised by preserved oxygen saturation, a ventilation–perfusion mismatch and increased alveolar ventilation/perfusion ratio heterogeneity, the underlying morphological evidence of this physiological enigma has not been fully understood. A compelling explanation for mosaic-like micro-ischaemia in the severe pathology of COVID-19 pneumonitis, which reflects the vasculopathy affecting the secondary lobule and the interlobular septae http://bit.ly/3GwMkII